Factors related to Musculoskeletal Disorders (MSDs) complaints in Mandonga wet market traders in Kendari City - Asnani Asnani; Yusuf Sabilu; La Ode Ahmad Saktiansyah (PT WIM Solusi Prima, 2026)
Musculoskeletal disorders—problems with the musculoskeletal system—cause pain, stiffness, and discomfort in certain parts of the body due to non-ergonomic work practices. Among vendors at the Mandonga Wet Market in Kendari, it is suspected that MSD complaints arise from improper work practices, such as bending over, standing for too long, and repeatedly lifting heavy objects. This study aims to identify factors associated with Musculoskeletal Disorders (MSDs) among vendors at the Mandonga Wet Market in Kendari in 2025. This is an analytical, observational study using a cross-sectional design. The sample size was 209 participants. Data were analyzed by testing the relationship between two variables using the Chi-Square test. The results indicate a significant association between age (p-value = 0.000) and MSD complaints, a significant association between work posture (p-value = 0.000) and MSD complaints, and a significant association between length of service (p-value = 0.000) and MSD complaints. However, there was no significant association between work duration (p-value = 0.320) and MSD complaints. It can be concluded that there is an association between age, work method, and duration of employment with musculoskeletal disorder (MSD) complaints; however, there is no association between duration of employment and musculoskeletal disorder (MSD) complaints among vendors at the Mandonga Wet Market in Kendari in 2025.